Simulação numérica do escoamento cruzado em cilindros em tandem dentro de um canal e proposta de correlação para o número de nusselt médio - Ferrari, Marco Aurélio (2015)
Evacuated tube collectors over the past years raised your use in domestic water heating applications. These heaters are made from various thermosyphons that collect the solar energy and transfer it to the water. The heat transfer occurs in a cross-flow of water over the thermosyphon condenser sections within a channel. The determination of the heat transfer rate can be done by using a Nusselt number correlation. However for the existing geometry in the evacuated tube collector, a correlation for Nusselt number is unknown. On this work, by numerical simulation, the influence of geometric parameters and the Reynolds number over the average of Nusselt number for the crossflow in tandem cylinder within a channel is done. Besides that, it is investigated the effect of channel width, distance between cylinders, number of cylinders. The transport equations are solved by computation fluid dynamic program ANSYS/FLUENT. The problem is not in steady state due the vortex formation in the back region of immersed bodies. The results showed that: (i) an increase in the distance between cylinders increase the average Nusselt number; (ii) The increase of channel width, has an opposite effect, reducing the Nusselt number instead of increasing;(iii) The increase of Reynolds number, evaluated between 80 and 200, increase the average Nusselt number; (iv) The average Nusselt number decreases with the increase of number of cylinders contained within the channel, but the average temperature in outlet raise. From obtained data, a new correlation for the average Nusselt number is suggested for the geometry investigated.